Senior leaders’ understanding of emotional intelligence and the experience of applying emotional intelligence competencies in a corporate environment in the Sub-Saharan Africa context - Legg, Benthe (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2023